Growth and characterization of layer by layer CdS–ZnS QDs on dandelion like TiO2 microspheres for QDSSC application. (August 2015) - Aslam, M. Mohamed; Ali, Syed Mansoor; Fatehmulla, Amanullah; Farooq, W.A.; Atif, M.; Al-Dhafiri, A.M.; Shar, Muhammad Ali
Abstract: Highly ordered mesoporous TiO2 nano-rod films modified by CdS and ZnS quantum dots (QDs) via successive ionic layer adsorption and reaction (SILAR) method were fabricated by hydrothermal technique. The nanorod assemblies of dandelion like TiO2 microsphere structures were grown uniformly over the FTO substrate without using any seeds or templates. The addition of CdS–ZnS QDs expands the photoresponse range of mesoporous TiO2 from ultraviolet region to visible range as confirmed by UV–vis spectrum. XRD studies revealed the characteristic peaks of TiO2 nanorods, CdS and ZnS QDs. FESEM images exhibited well-organized growth of nanorods with diameter ranging from 30 to 35 nm. FESEM and HRTEM images confirmed the presence of QDs embedded on TiO2 in cluster form. The fabricated cell measured a short circuit current ( J sc ) of 1.04 mA/cm 2 and an open circuit voltage ( V oc ) of 0.502 V at AM 1.5 illumination intensity. C – V measurements at different frequencies showed an ordered trend without any sharp fall or negative capacitance behavior.